A Two‐Dimensional Semiconductive Metal‐Organic Framework for Highly Efficient Microwave Absorption. Issue 4 (21st December 2021) - Miao, Peng; Zhang, Tao; Wang, Teng; Chen, Juan; Gao, Tong; Wang, You; Kong, Jie; Chen, Kai‐Jie
Comprehensive Summary: Advanced microwave absorbing materials (MAMs) are urgently required to eliminate and attenuate microwaves to address the ubiquitous microwave radiations and interference. In this contribution, we report the microwave absorption application of a two‐dimensional (2D) semiconductive metal‐organic framework (MOF), i.e., CuHT (HT = 4‐hydroxythiophenol), without any pyrolysis at high temperature. Owing to the suitable electrical conductivity (2.69 × 10 –4 S·cm –1 ), CuHT renders remarkable microwave absorption performance, with the minimum reflection loss ( RL min ) of –50.9 dB and the effective absorption bandwidth of 4.2 GHz (7.7—10.9 GHz) at a thickness of 1.74 mm. Based on DFT calculation, microwave attenuation is mainly originated from resistance loss due to the conducting planes of honeycomb‐like Cu2 S layers. Thanks to the facile kilogram‐scale synthesis, CuHT holds great potential for future microwave absorption applications. Abstract : A semiconductive metal organic framework with feasible scale‐up production ability was straightforwardly applied as the effective microwave absorbing material.